Chimeric antigen receptor T‐cell therapy combined with autologous stem cell transplantation improved progression‐free survival of relapsed or refractory diffuse large B‐cell lymphoma patients: A single‐center, retrospective, cohort study. Issue 4 (22nd February 2022) - Wang, Tao; Xu, Lili; Gao, Lei; Tang, Gusheng; Chen, Li; Chen, Jie; Wang, Yang; Fu, Weijia; Yue, Wenqin; Ye, Mingyu; Yu, Jiechen; Yu, Xuejun; et al.
Abstract: Autologous hematopoietic stem cell transplantation (ASCT) and chimeric antigen receptor T ‐cell therapy (CART) are salvage therapies that are utilised for treatment of relapsed or refractory (R/R) diffuse large B ‐cell lymphoma (DLBCL). However, whether the combination therapy of ASCT and CART (ASCT‐CART) can improve the survival of R/R DLBCL remains unknown. Overall, 67 R/R DLBCL patients were included, among which 21 patients underwent ASCT‐CART therapy and 46 patients underwent ASCT therapy. The median number of mononuclear cells numbers that were infused in the ASCT‐CART and ASCT groups was 4.71 × 10 8 /kg and 5.36 × 10 8 /kg, respectively ( p = 0.469). The median number of CD34 + cell numbers that were infused in the ASCT‐CART and ASCT groups was 2.41 × 10 6 /kg and 3.05 × 10 6 /kg, respectively ( p = 0.663). The median number of CART cells that were infused was 2.63 × 10 6 /kg with a median transduction rate of 59.83%. The objective response rates to ASCT‐CART and ASCT therapy were 90% and 89%, respectively ( p = 1.000). However, the ASCT‐CART group showed higher complete remission (CR) rates than the ASCT group (71% vs. 33%; p = 0.003). The ASCT‐CART group demonstrated superior 3 year progression‐free survival (PFS) (80% vs. 44%; p = 0.036) and lower 3 year relapse/progression rate (15% vs. 56%; p = 0.015) compared to the ASCT group. However, the 3 year overall survival results indicated that there were no differences between the two groups (80% vs. 69%; p = 0.545). For R/R DLBCL patients, ASCT‐CART therapy is associated with higher CR rate, better PFS, and lower relapse/progression rate. These data support that ASCT‐CART therapy can be used as a salvage therapy for R/R DLBCL patients.